1999
DOI: 10.1161/01.atv.19.4.1004
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Hyaluronan- and Versican-Rich Pericellular Matrix Is Required for Proliferation and Migration of Vascular Smooth Muscle Cells

Abstract: The accumulation of hyaluronan (HA) and the HA-binding proteoglycan versican around smooth muscle cells in lesions of atherosclerosis suggests that together these molecules play an important role in the events of atherogenesis. In this study we have examined the formation of HA- and versican-rich pericellular matrices by human aortic smooth muscle cells in vitro, using a particle-exclusion assay, and the role of the pericellular matrix in cell proliferation and migration. The structural dependence of the peric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
363
2
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 453 publications
(391 citation statements)
references
References 52 publications
23
363
2
3
Order By: Relevance
“…The converse experiments using antisense or siRNA also indicate that endogenous versican V1 increases proliferation, including that of SMCs , Huang et al 2006) (unpublished data, Rahmani M, Wong B, Allahverdian S, Cheung C, Carthy J, Keire P, Wight T, McManus B). These data are consistent with evidence that formation of versican-hyaluronan pericellular matrix is required for SMC proliferation and migration (Evanko et al 1999). Versican V1 may enhance proliferation via increased levels of the EGF receptor and ERK activation coupled with loss of the cell-cycle inhibitor p27 (unpublished data, Rahmani M, Wong B, Allahverdian S, Cheung C, Carthy J, Keire P, Wight T, McManus B) (Sheng et al 2005).…”
Section: Possible Role Of Versican Breakdown Products In Vascular Dissupporting
confidence: 84%
“…The converse experiments using antisense or siRNA also indicate that endogenous versican V1 increases proliferation, including that of SMCs , Huang et al 2006) (unpublished data, Rahmani M, Wong B, Allahverdian S, Cheung C, Carthy J, Keire P, Wight T, McManus B). These data are consistent with evidence that formation of versican-hyaluronan pericellular matrix is required for SMC proliferation and migration (Evanko et al 1999). Versican V1 may enhance proliferation via increased levels of the EGF receptor and ERK activation coupled with loss of the cell-cycle inhibitor p27 (unpublished data, Rahmani M, Wong B, Allahverdian S, Cheung C, Carthy J, Keire P, Wight T, McManus B) (Sheng et al 2005).…”
Section: Possible Role Of Versican Breakdown Products In Vascular Dissupporting
confidence: 84%
“…Assembly of HA-rich, hydrated matrices around the cells stimulates migration [32] and tumor cell-HA interactions mediated through CD44 may play roles in facilitating migration through the tumor associated HA-rich matrix [3]. Formation of hydrated, HA-rich matrix was disrupted in antisense treated cells, as visualized by the particle exclusion assay, resulting in reduced motility and invasiveness in this study.…”
Section: Discussionmentioning
confidence: 76%
“…[41][42][43] Our finding that treatment of VSMCs with heparinase suppresses LPL-induced VSMC proliferation suggests that LPL binding to HSPGs expressed on the VSMC surface is essential for its effect on cell proliferation. However, because the formation of a proteoglycan-rich pericellular matrix may be involved in VSMC proliferation, 44 inhibition of VSMC growth by heparinase treatment of the cells could also be due to alteration of the extracellular matrix integrity. Recently, Silver et al 45 showed that locally delivered heparinase reduced medial VSMC proliferation induced by balloon catheter injury in rat carotid arteries.…”
Section: Discussionmentioning
confidence: 99%